Authors Preparing Papers for the Journal Ekonomika Should be Aware That - Žurnalas, Ekonomika (Ekonomika, 2003)
The journal Ekonomika (established and published by Vilnius University) is designated as a scientific publication for the dissemination of doctoral dissertations and works of habilitation (Science and Studies Department to the Ministry of Education and Science order 01 05 1998 No. 13, confirmed by the Lithuanian Science Council 10 November 1997 decision No. 111-39).